A novel developed method based on single primer isothermal amplification for rapid detection of Alicyclobacillus acidoterrestris in apple juice. (May 2017) - Yang, Yue; Yang, Qian; Ma, Xiaoyan; Zhang, Yunzhe; Zhang, Xianzhou; Zhang, Wei
Abstract: Alicyclobacillus acidoterrestris ( A. acidoterrestris ), as one of the most major spoilage-causing species within the Alicyclobacillus genus, can survive and multiply in the pasteurization process. Nowadays, A. acidoterrestris has become worldwide issue in the fruit juice industry due to its spore-forming and thermo-acidophilic features. A novel single primer isothermal amplification assay (SPIA) was developed for the rapid detection of A. acidoterrestris in apple juice. This assay was designed to target the 16S rRNA gene with a DNA/RNA chimeric primer. Detection of gene amplification was accomplished by amplification curve, turbidity and addition of single strand DNA binding dye SYBR Green II allowing visualization under ultra violet light. The specificity of the assay was confirmed using 7 strains of A. acidoterrestris and 30 strains of non- A. acidoterrestris . The SPIA was highly sensitive and the detection limit was as low as 4.8 CFU/mL. Furthermore, the apple juice inoculated with 61 CFU/mL of A. acidoterrestris could be detected as positive. The novel SPIA with visualization results was successfully applied for the detection of A. acidoterrestris and exhibited high specificity and sensitivity, making it a powerful tool for the detection of A. acidoterrestris in fruit juice industry and being conveniently applied in developing countries with limited resource. Highlights: A rapid and visual SPIA method was firstly developed for the detection of Alicyclobacillus acidoterrestris. The detection results of SPIA assay was observed by fluorescence under UV light and turbidity by naked eyes. The SPIA assay exhibited higher sensitivity and detection limit than conventional PCR. The SPIA method was validated with artificially contaminated apple juice sample.